2022
DOI: 10.1002/dev.22245
|View full text |Cite
|
Sign up to set email alerts
|

Event‐related potentials data quality in young children: Standardized measurement error of ERN and Pe

Abstract: Most methods used to quantify event-related potential (ERP) data were developed for use with typical adult populations. Questions regarding how these methods apply to child ERP data remain. Here, we focused on two widely used ERP scoring methods, namely, time-window mean amplitude and peak amplitude measures, for two ERP error monitoring components, the error-related negativity (ERN) and the error positivity (Pe), collected from Kindergarteners during a child-friendly cognitive control task (N = 170). We first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 70 publications
(135 reference statements)
0
5
0
Order By: Relevance
“…It would be very helpful for researchers to provide SME benchmarks for other paradigms, participant populations, and scoring procedures. For example, a recent study by Isbell and Grammer (2022) examined the SME for the ERN in children between the ages of 5 and 7 using a child‐friendly version of the Go/NoGo task. They found that the SME values were substantially larger than those found for the ERN in the present study, which is not surprising given the challenges involved in recording the EEG from children.…”
Section: Discussionmentioning
confidence: 99%
“…It would be very helpful for researchers to provide SME benchmarks for other paradigms, participant populations, and scoring procedures. For example, a recent study by Isbell and Grammer (2022) examined the SME for the ERN in children between the ages of 5 and 7 using a child‐friendly version of the Go/NoGo task. They found that the SME values were substantially larger than those found for the ERN in the present study, which is not surprising given the challenges involved in recording the EEG from children.…”
Section: Discussionmentioning
confidence: 99%
“…Their work demonstrates the likely differences in ERP morphologies that are present in the extant developmental literature and the need for empirically derived gold standard editing practices for work with children. Isbell and Grammer (2022) describe an approach to quantifying ERP data quality using standardized measurement error, which can be used to consider the impact of different processing and scoring decisions on data quality and as a more objective method of deciding when to exclude participants’ data due to noise.…”
Section: New Approaches To Data Processing and Quantificationmentioning
confidence: 99%
“…We conducted Independent component analysis (ICA) to decompose independent components based on all electrodes except for VEOG, HEOG, and two mastoid electrodes. By using the ICLabel plug‐in (Pion‐Tonachini, Kreutz‐Delgado & Makeig, 2019), the artifacts generated from eyes, muscle, heart, line noise, and channel noise were corrected when their artifacts probability was over 70% and associated with the “Brain” label with <5% probability (Isbell & Grammer, 2022).…”
Section: Methodsmentioning
confidence: 99%